Development and validation of a patient-reported outcome instrument for skin involvement in patients with systemic sclerosis. Issue 8 (17th February 2017) - Man, Ada; Correa, Jeannette K; Ziemek, Jessica; Simms, Robert W; Felson, David T; Lafyatis, Robert
Abstract : Objectives: We developed a patient-reported outcome (PRO) instrument to assess the skin-related quality of life in patients with systemic sclerosis (SSc). Methods: Participants with SSc provided input on skin-related health effects through focus groups. We developed items for scleroderma skin PRO (SSPRO) to encompass these effects. Further consideration from cognitive interviews and an expert panel led to reduction and modification of items. A 22-item SSPRO was field tested. Psychometric analysis included test–retest reliability, internal consistency and exploratory factor analysis (EFA). Construct validity was assessed through correlation with other participant and physician-assessed measures. Results: 140 participants completed the SSPRO: mean age was 53.4 years, median disease duration was 5 years, 82.1% were female and 32.9% had diffuse cutaneous SSc. EFA supported four factors in SSPRO corresponding to hypothesised constructs: physical effects, physical limitations, emotional effects and social effects. Removal of 4/22 items resulted in acceptable goodness-of-fit statistics. Test–retest reliability (intraclass correlation coefficient=0.61–0.83) was moderate to high and internal consistency (Cronbach's α=0.89–0.96) was high. SSPRO correlated strongly with other participant-reported measures (r=0.59–0.88) suggesting construct validity, and less well with physician-assessed measures (r=0.31–0.40). SSPRO scores were significantly different for each level of participant-reported skin severity, and for limited versus diffuse cutaneous SSc. Conclusions: SSPRO has been developed with extensive patient input and demonstrates evidence for reliability and validity. It is complementary to existing measures of SSc skin involvement with emphasis on the patient's experience. Further research is needed to assess its sensitivity to change.